Post-privatization state ownership and bank risk-taking: Cross-country evidence - Boubakri, Narjess; El Ghoul, Sadok; Guedhami, Omrane; Hossain, Mahmud (Journal of Corporate Finance, 2020)
We examine the relation between state residual ownership and bank risk-taking for privatized banks from 45 countries. Applying propensity score matching, we find that privatized banks tend to exhibit higher levels of risk-taking post-privatization than their publicly listed non-privatized counterparts. Moreover, partially privatized banks exhibit higher levels of risk-taking than fully privatized banks. We also observe a positive and significant relation between the level of residual state ownership and risk-taking. These findings are consistent with the distorted objectives associated with government control, as suggested by the political benefits of control, and with the soft budget constraint views of state ownership. The distortion can be mitigated by the quality of a country's institutional and regulatory environments. Finally, our results show that the effect of state ownership on risk-taking is more pronounced in countries with a higher dominance of state-owned enterprises, and it was more prevalent during the global financial crisis.